Surgical resection of symptomatic brain metastases improves the clinical status and facilitates further treatment. (28th August 2020) - Schödel, Petra; Jünger, Stephanie T.; Wittersheim, Maike; Reinhardt, Hans Christian; Schmidt, Nils‐Ole; Goldbrunner, Roland; Proescholdt, Martin; Grau, Stefan
Abstract: Background: Brain metastases (BM) frequently cause focal neurological deficits leading to a reduced Karnofsky performance score (KPS). Since KPS is routinely used to guide the choice of adjuvant therapy, we hypothesized that improving KPS by surgical resection may improve the chance for adjuvant treatment and ultimately result in better survival. We therefore analyzed the course of a large cohort undergoing resection of symptomatic brain metastases in the context of further treatment and clinical outcome. Patients and methods: In a bi‐centric retrospective analysis we retrieved baseline, clinical, and treatment‐related parameters of patients operated on BM between 2010 and 2019. Survival was calculated using Kaplan‐Meier estimates; prognostic factors for survival were analyzed by Log‐rank test and Cox proportional hazards. Results: We included 750 patients with a median age of 61 (19‐87) years. The functional status was significantly improved by surgical resection, with a median preoperative (KPS) of 80 (10‐100) increasing to 90 (0‐100) after surgery ( P  < .0001). Moreover, surgery improved the RTOG recursive partitioning analysis (RPA) class from III to I/II in 82 patients. Postoperative local radiotherapy and systemic treatment were associated with significantly longer survival ( P  < .0001 for each). Systemic treatment was provided significantly more frequently in patients with a fair postoperative clinical status (KPS ≥ 70; P  < .0001). The postoperative clinical status, postoperative radiotherapy, systemic treatment, controlled systemic disease and < 4 BM were independent predictors for survival. Conclusion: The resection of symptomatic BM may restore clinical status, so enhancing the likelihood of receiving adjuvant treatment, and therefore leading to improved overall survival. Abstract : In patients with symptomatic brain metastases systemic oncological treatment is the strongest factor for further survival. Resection of a symptomatic brain metastasis results in an improved clinical status which facilitates further treatment.